Hazard Prevention, Death and Dignity During COVID-19 Pandemic in Italy - Ussai, Silvia; Armocida, Benedetta; Formenti, Beatrice; Palestra, Francesca; Calvi, Marzia; Missoni, Eduardo (Frontiers in Public Health, 2020)
On 9 March 2020, Italy passed the Prime Minister's Decree n. 648, establishing urgent measures to contain the transmission of COVID-19 and prevent biological hazards, including very restrictive interventions on public Holy Masses and funerals. Italy banned burial procedures based (i) on the recent acknowledgment about the virus environmental stability as well as (ii) its national civil contingency plan. Hence, only the cremation process is admitted for COVID-19 deaths. Viewing of the body is permitted only for mourners, which are allowed to perform the prayer at the closing of the coffin and the prayer at the tomb (cf. Rite of Succession, first part n. 3 and n. 5). The dead cannot be buried in their personal clothes; however, priests have been authorized to put the family clothes on top of the corpse, as if they were dressed. Burying personal items is also illegal. The dignity of the dead, their cultural and religious traditions, and their families should be always respected and protected. Among all the threats, COVID-19 epidemic in Italy revealed the fragility of human beings under enforced isolation and, for the first time, the painful deprivation of families to accompany their loved ones to the last farewell. Ethics poses new challenges in times of epidemics.